Identification of Land Movement Safety Factors on the Slope of Lolak Dam - Sutriyono sutriyono; Ahmad Zainuri; Muhammad Kasim (Journal of Earth Energy Science, Engineering, and Technology, 2021)
North Arm Sulawesi is a triple junction between three convergent plates which results in development of geological structures at all scales, thereby triggering the potential for land motion. Lolak Dam is an infrastructure that functions as a water reservoir which is then channeled for domestic needs. This research aims to identify safety factors of the Lolak Dam slopes where land motion occurs several times. Field data in the form of lithology was carried out by geomechanical testing in the form of specific gravity, cohesion, and internal shear angle. The analysis was carried out on the slopes of the Lolak Dam on the left backrest which is a spillway area. The method used is Bishop with the help of the Slide v.6 Program. Lithological in the research area obtained gray claystone, red claystone, chert slate, sandstone, and basalt. Safety factors result which using the Slide program are 1.517 (Stable) in slope 1, 1,260 (Stable) in slope 2, and 0.745 (unstable) in slope 3.